Integrasi Spiritual dan Empiris dalam Pendidikan: Studi Perbandingan antara Pemikiran Ibnu Taimiyah dan Albert Bandura - Edo Ferdian; Malik Ashari; Syamsul Arifin; Febry Suprapto (Educational Research Center, 2025)
This research aims to analyze and compare the thoughts of Ibnu Taimiyah and Albert Bandura in the context of educational philosophy in order to formulate an integrative education model that combines spiritual and empirical dimensions. This research uses a qualitative approach with a comparative-analytic type of literature study. Data was obtained from the primary works of the two figures and secondary sources such as scientific journals and books, then analyzed using the Miles and Huberman model. The research results show that Ibn Taimiyah emphasized education as a spiritual transformation based on monotheism, morals and nature, while Bandura emphasized the formation of behavior through observation, imitation and reinforcement. The integration of the two gave birth to the Spiritual-Empirical Integrative Education Model which balances the values ​​of faith and empirical methods, making education a means of forming people with faith, knowledge and morals. This model is relevant for bringing back the spiritual spirit in modern education